Lactobacillus plantarum alleviates high-fat diet-induced obesity by altering the structure of mice intestinal microbial communities and serum metabolic profiles - Zhu, Junwen; Liu, Xueying; Liu, Naiyuan; Zhao, Ruochi; Wang, Shuangshuang (Frontiers in Microbiology, 2024)
Obsesity, which is always accompanied by disorders of lipid metabolism and dysbiosis of the gut microbiota, has become a global epidemic recognised by the World Health Organisation, necessitating innovative strategies and a globally accepted agreement on treating obesity and its related complications. Probiotics, as major active ingredients in many foods, offer potential as biological treatments for obesity prevention and management. Lactobacillus plantarum (L. plantarum) possesses a wide range of biological activities and is widely used to alleviate and ameliorate various diseases. This research demonstrated that Lactobacillus plantarum reduces the weight increase and fat build-up caused by a high-fat diet (HFD) in mice, while also improving glucose tolerance and insulin sensitivity in obese mice. Results indicated that L. plantarum effectively controlled the intestinal microbial community's structure, counteracted disruptions in gut flora caused by HFD, normalized the Firmicutes to Bacteroidota ratio (F/B), and decreased the prevalence of detrimental bacteria Desulfovibrio and Clostridia. Serum metabolomics findings indicate notable alterations in serum metabolites across various groups, notably the increased levels of Isoprothiolane and Inosine, key regulators of lipid metabolism disorders and enhancers of fat burning. These differential metabolites were mainly enriched in unsaturated fatty acid biosynthesis, sulfur metabolism, fatty acid biosynthesis, and purine metabolism.Consequently, we propose that L. plantarum has the potential to alter the gut microbial community's composition, positioning it as a promising option for obesity therapy.